Reponse-reinforcer independence and conventional extinction after fixed-interval and variable-interval schedules - Lattal, Kennon A. (1972)
After training three albino rats to bar press during a multiple fixed-interval variable-interval schedule, the response-reinforcer dependency was simultaneously removed from both components, converting the schedule to multiple fixed-time variable-time. Response rates were reduced in both components under these conditions but the fixed-time schedule maintained relatively higher response rates with each rat. After reinstating the response-reinforcer dependency in both components, responding was conventionally extinguished by rendering the pellet dispenser inoperative. Responding rapidly decreased to near-zero levels. Differences in fixed and variable-time schedules in sustaining behavior are discussed in terms of differences in response rates at the time of reinforcer delivery. Similarities and differences between conventional extinction and schedules delivering response-independent reinforcers are also discussed.